A comparative assessment on the effect of 1-propanol and 1-hexanol as oxygenated additive with diesel/biodiesel blends on single cylinder diesel engine characteristics. Issue 1 (February 2022) - Jayapal, Mohanraj; Radhakrishnan, Kannan G
Recovery of energy from waste is appealing as it meets the energy demand and minimize the problems associated with waste management. Biodiesel derived from waste cooking oil was used in this study along with 1-propanol and 1-hexanol to make a comparative assessment of the alcohol addition on different diesel engine characteristics. Experimental trials were carried out by utilizing two ternary blends with 20% by volume of higher alcohols (propanol & hexanol), 30% by volume of biodiesel and 50% by volume of diesel. Later, the results were compared with binary blend of 50% by volume of diesel and 50% by volume of biodiesel (D50B50), pure diesel (D100) and biodiesel (B100). Results divulge that ignition delay period got longer for both Pr20 blend and HX20 blend which resulted in a 2% and 1% increase in peak cylinder pressure and 26% and 15% increase in peak heat release rate respectively against D50B50 blend operation. In comparison with the binary blend, the engine brake thermal efficiency improved by 3% and deteriorated by 2% against hexanol and propanol blend respectively. The NOx emission aggravated with ternary blends, nearly 8% higher NOx emission was observed for propanol blend when compared to hexanol blend. Both smoke opacity and carbon monoxide emission reduced, while unburnt hydrocarbon emission was on the higher side with the introduction of alcohol. It is concluded from the observations that the HX20 blend was found to be optimal in terms of improved engine performance and emission characteristics.